Developing Science Fiction among Kindergarten Children - amany Hassanein; Randa El deeb; Abdul Malik Taha (International Journal of Instructional Technology and Educational Studies)
The aim of the current research is to verify the possibility of developing science fiction skills among kindergarten children by using some scientific concepts that can develop science fiction among kindergarten children and preparing a set of scientific activities that work to develop that kind of imagination among kindergarten children, the research sample included second-level children From kindergarten from 5-6 years, where the number of kindergarten children was (30), and the period of application of the program was three times a week for a period of three months, and the study tools included (science fiction scale - a note card for children during science fiction activities). The results of the study in the presence of a statistically significant difference between the mean scores of the children in the pre- and post-application in favor of the post-sci-fi scale